2021
DOI: 10.1039/d0cc07565e
|View full text |Cite|
|
Sign up to set email alerts
|

RuCo alloy trifunctional electrocatalysts with ratio-dependent activity for Zn–air batteries and self-powered water splitting

Abstract: Herein, we reported a RuCo alloy with nitrogen-doped porous carbon (RuCo/NPC) as efficient trifunctional electrocatalysts for Zn–air batteries and water splitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…This result is consistent with a previous study that reported the formation of hcp-structured Ru–Co alloys . Also, a recent experimental study shows that the RuCo-alloyed structure can be readily synthesized …”
Section: Methodssupporting
confidence: 93%
See 1 more Smart Citation
“…This result is consistent with a previous study that reported the formation of hcp-structured Ru–Co alloys . Also, a recent experimental study shows that the RuCo-alloyed structure can be readily synthesized …”
Section: Methodssupporting
confidence: 93%
“…11 Also, a recent experimental study shows that the RuCo-alloyed structure can be readily synthesized. 12 Then, several 2 × 2 × 1 supercells of the B h structure were optimized to model the RuCo(0001) surface, in which various atomic configurations were considered (Table S2, Supporting Information), and the S4 surface structure was found to be most thermodynamically favorable. The notations for the adsorption sites on RuCo(0001) with the S4 structure are given in Figure S1, Supporting Information.…”
Section: ■ Methodsmentioning
confidence: 99%
“…This core–shell nanostructure can not only improve the conductivity but also provide more accessible active sites and protect the metal-based active species during the catalytic process. Moreover, the lattice fringes with a spacing of 0.22 and 0.208 nm corresponds to the (100) and (002) planes of RuCo alloy, while the lattice spacing with 0.255 and 0.291 nm corresponds to the (101) and (220) planes of RuO 2 and Co 3 O 4 , respectively, revealing the coexistence of RuCo alloy, RuO 2 , and Co 3 O 4 in RuCo-LNC-120. Similarly, note that the lattice spacing of 0.475 nm, corresponding to the (111) plane of spinel Co 3 O 4 , is larger than the theoretical value (0.467 nm), speculating that Ru 4+ may be doped into the Co 3 O 4 microstructure.…”
Section: Resultsmentioning
confidence: 98%
“…Unfortunately, high cost and resource scarcity have restricted their large-scale applications. [15][16][17][18][19] Consequently, the search for inexpensive and high-performance OER electrocatalysts is inevitable for advanced energy devices, but challenging. [20][21][22] Recently, much work has been done to develop highefficient and low-cost OER electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%